2018
DOI: 10.1136/jnnp-2018-318756
|View full text |Cite
|
Sign up to set email alerts
|

Age at onset of genetic (E200K) and sporadic Creutzfeldt-Jakob diseases is modulated by the CYP4X1 gene

Abstract: We identified two single nucleotide polymorphisms on the gene locus as candidate disease modifiers in patients with E200K CJD of the cluster area and confirmed this finding in 32 patients with E200K CJD from non-cluster areas and 259 patients with sporadic CJD. Our results indicate that the gene modulates the onset of disease in patients with E200K genetic and sporadic CJD. This finding improves our understanding on the pathogenesis of CJD, suggests new targets for developing novel therapeutic strategies and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…This is supported by previous studies, which showed wide variation of PrP expression in healthy control brains [ 23 ]. This may explain why some carriers of the E200K mutation do not develop the disease as well as why the clinical signs [ 24 ], age of clinical onset, and duration of clinical disease vary between individuals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by previous studies, which showed wide variation of PrP expression in healthy control brains [ 23 ]. This may explain why some carriers of the E200K mutation do not develop the disease as well as why the clinical signs [ 24 ], age of clinical onset, and duration of clinical disease vary between individuals [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further genetic modifiers may also influence disease onset, duration and signs. For instance, CYP4X1 gene has been recently found to modulate the age of onset in individuals with the E200K mutation [ 25 ]. The influence of genetic background on E200K prion disease is also shown by the difference in the outcomes of the two mouse models of E200K prion disease.…”
Section: Discussionmentioning
confidence: 99%
“…In several forms of genetic prion disease, for example those associated with the E200K PRNP mutation, the clinical disease manifestations, PrP res WB signature and tissue PrP res distributions are similar to that in sCJD [34,48]. Despite the ethical issues it might raise, the longitudinal collection of blood samples and body fluids, for research purposes, in consenting patients belonging to families affected by these genetic forms of prion diseases (with confirmed mutations of the PRNP gene) may represent the only possibility to address this question.…”
Section: Iatrogenic Transmission Of Cjdmentioning
confidence: 93%
“…The onset and clinical characteristics of Chinese E200K gCJD are more like as sCJD, although the onset age of E200K gCJD is younger than that of sCJD 8,17 . CYP4X1 SNP rs9793471 has an influence on age at onset of disease in patients with E200K genetic and sporadic CJD 18 . In this study, twenty nine cases were CYP4X1 rs9793471 AA genotype, and only one case was GA.…”
Section: Discussionmentioning
confidence: 99%